Book review: The Confucian world observed: A contemporary discussion of Confucian humanism in East Asia by Tu Weiming, Milan Hejtmanek, and Alan Wachman - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 1995)
ucian Humanism" in 1989, the objective of which was "to explore Confucian ethics as a common intellectual discourse in East Asia from a multidisciplinary and cross-cultural perspective" (p. vii), this volume offers a summary of the three-day event. If one were looking for "essays" on Confucian ethics, one would not find them here. With one exception where a participant sent in a written clarification, the report is based on recordings of the wide-ranging discussions that transpired at the workshop. What one will find are serious and often provocative reflections on a complex phenomenon by a group of eminent scholars from both the Humanities and Social Sciences. While there are few sustained arguments or even dialogues, it is instructive to see how different scholars approach issues of common concern from vastly different perspectives.